2019
DOI: 10.1002/jcb.28891
|View full text |Cite
|
Sign up to set email alerts
|

Halting ionic shuttle to disrupt the synthetic machinery—Structural and molecular insights into the inhibitory roles of Bedaquiline towards Mycobacterium tuberculosis ATP synthase in the treatment of tuberculosis

Abstract: Therapeutic targeting of the adenosine triphosphate (ATP) machinery of Mycobacterium tuberculosis (Mtb) has recently presented a potent and alternative measure to halt the pathogenesis of tuberculosis. This has been potentiated by the development of bedaquiline (BDQ), a novel small molecule inhibitor that selectively inhibits mycobacterial F1Fo‐ATP synthase by targeting its rotor c‐ring, resulting in the disruption of ATP synthesis and consequential cell death. Although the structural resolution of the mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
(136 reference statements)
1
3
0
Order By: Relevance
“…The generation of a steady‐state had confirmed that the systems performed during MD simulation were stable and hence further analysis could be performed. As seen in previous studies, a relatively high RMSD generated for a simulated system usually relates to structural instability, whereas a lower RMSD relates to a more stable system [62] . On average, m IDH1 and m IDH2 in their apo conformation revealed higher atomic deviation with RMSD values of 3.94 Å and 5.15 Å, whereas the AG‐881 bound systems of m IDH1 and m IDH2 exhibited lower RMSD values of 3.16 Å and 3.65 Å, respectively.…”
Section: Resultssupporting
confidence: 61%
“…The generation of a steady‐state had confirmed that the systems performed during MD simulation were stable and hence further analysis could be performed. As seen in previous studies, a relatively high RMSD generated for a simulated system usually relates to structural instability, whereas a lower RMSD relates to a more stable system [62] . On average, m IDH1 and m IDH2 in their apo conformation revealed higher atomic deviation with RMSD values of 3.94 Å and 5.15 Å, whereas the AG‐881 bound systems of m IDH1 and m IDH2 exhibited lower RMSD values of 3.16 Å and 3.65 Å, respectively.…”
Section: Resultssupporting
confidence: 61%
“…Notably, sabinene and genistin had the lowest RMSD averages of 1.48 Å and 1.44 Å respectively for the terpenes and flavonoids, correlating to the compounds that enacted the most structural stability. In most structural studies, a higher average RMSD correlates to a less stable structural conformation and vice versa as employed in various studies (Abdullahi et al, 2018;Salifu et al, 2019). According to (Ramírez & Caballero, 2018), RMSD < 2.0 Å corresponds to good docking solutions.…”
Section: Discussionmentioning
confidence: 99%
“…This is in reference to some of the compounds (alpha-pinene, alpha-terpinene, 3-carene, phytol, sabinene, apigenin, biacelein, genistin, phloretin and quercetin) exhibiting less flexibility on the SdiA structure while other compounds such as beta-pinene, camphene, isoterpinene, p-cymene, diadzein, fisetin and glycitein proved to be highly flexible relative to the unbound SdiA state. The substantial difference in structural flexibility of the bound terpenes and flavonoids in contrast to the unbound SdiA could play a crucial role in the biological activity of the protein (Salifu et al, 2019), as the binding of the compounds may result in a more flexible or more rigid SdiA structure which directly impacts the native state of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study showed that multiple BDQ molecules can be bound to the c-ring simultaneously, depending on the drug's concentration [42]. While bound to the c-ring, interplay between BDQ molecules can occur, as suggested by the recent finding that c-ring binding affinity of a BDQ molecule is increased when there is complementary binding of an additional BDQ molecule [45].…”
Section: Stalling Of Rotation Of the Mycobacterial F-atp Synthase C-ringmentioning
confidence: 99%